Natural sensitizers for solar cell based on gel polymer electrolytes containing iodide/triiodide redox couple / Marziyeh Alinejad - Marziyeh , Alinejad (2022)
Polyvinyl alcohol (PVA) based gel polymer electrolytes (GPEs) containing iodide/triiodide have been prepared. Two types of solvents namely dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) have been used in the preparation of the GPEs. The GPEs are (i) DMF/PVA/KI/I2, (ii) DMF/PVA/KI/I2/4-tert-butylpyridine (TBP), (iii) DMSO/PVA/KI/I2 and, (iv) DMSO/PVA/KI/I2/TBP. The ionic conductivity of GPEs at different temperatures have been determined from the electrochemical impedance spectroscopy (EIS) measurement. X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) have been performed to analyze the structural properties of the GPEs. All GPEs have been tested for dye-sensitized solar cell (DSSC) with natural sensitizers extracted from different natural sources namely blackberry, blueberry, raspberry and saffron. DSSCs have been characterized with J-V measurement, EIS, Intensity modulated photocurrent spectroscopy (IMPS), and Intensity modulated photovoltage spectroscopy (IMVS). The GPEs without TBP shows the ionic conductivity of (14.05±3.50) mS cm-1 for DMF GPE and (2.45±1.51) mS cm-1 for DMSO GPE. The addition of TBP does not improve the ionic conductivity of the GPE with (11.99±6.84) mS cm-1 for DMF GPE and (2.98±1.35) mS cm-1 for DMSO GPE. DSSCs have been fabricated by sandwiching GPE in between photoanode and platinum counter electrode. The photoanode has been prepared by coating two layers of TiO2 on fluorine doped tin oxide (FTO) substrate via doctor blade method and sensitized with natural sensitizer. DMF/PVA/KI/I2/TBP GPE exhibit the best performance in DSSC with anthocyanin dye system. The best performance of DSSC can be explained via the charges transfer resistance, electron transfer time and electron recombination time from the EIS, IMPS and IMVS data respectively.